Pengaruh Inflasi Dan Produk Domestik Bruto (PDB) Terhadap Tingkat Imbalan Sertifikat Bank Indonesia Syariah (SBIS) Tahun 2009-2012 - Sri Mahrani; Rahmat Richard; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of inflation and Gross Domestic Product (GDP) of the Certificate of Bank Indonesia Sharia (SBIS). This study uses secondary data obtained from the website of Bank Indonesia publications and Statistics Indonesia. This study was conducted nationally, namely Indonesia in the first quarter of 2009 until the fourth quarter of 2012. This study used a multiple linear regression analysis using the computer program SPSS version 16.0. This study consisted of two independent variables (inflation and GDP) and one dependent variable (Bank Indonesia Sharia Certificate). The results obtained are inflation and GDP together (simultaneous) effect on Bank Indonesia Sharia Certificate with a significance level of 5%. Partially Inflation has a significant positive effect on the Certificates of Bank Indonesia Sharia, while the GDP variable is partially significant negative effect on Bank Indonesia Sharia Certificate. Variation factors that affect the Bank Indonesia Sharia Certificate explained by inflation and GDP are jointly influenced by 75.4% (R2 = 0.754) while the remaining 24.6% is explained by other variables not included in the study. Of the two variables (inflation and GDP) GDP variables that significantly influence the Bank Indonesia Sharia Certificate, ie with t -5.398 and a significance value of 0.000.Keywords: Inflation, Gross Domestic Product (GDP), and Certificate of Bank Indonesia Sharia (SBIS).